Beckman MMC Horizon Systems Metabolic Measurement Cart (1975)
Beckman Instruments introduced the Metabolic Measurement Cart (MMC) in 1975. The programmable system could automatically test oxygen, carbon dioxide, barometric pressure, expired air volume and temperature, and print results as the test progressed.
Keywords: Medical laboratories--Equipment and supplies; Scientific apparatus and instruments; Metabolism--Testing; Beckman Instruments, Inc.